2002
DOI: 10.1108/03090560210437334
|View full text |Cite
|
Sign up to set email alerts
|

How does market orientation contribute to service firm performance?

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
123
0
7

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(148 citation statements)
references
References 75 publications
9
123
0
7
Order By: Relevance
“…Innovation resources have been shown to mediate the relationship between market orientation and organizational performance (e.g., Han, Kim, & Srivastava, 1998). Cravens and Guilding (2000) and Matear, Osborne, Garrett, and Gray (2002) suggested that reputational resources may also mediate this relationship. We propose and test a conceptual model in which the infl uence of market orientation on fi nancial and market performance is mediated through reputational and innovation resources.…”
Section: Cette éTude Examine Les Relations Entre L'orientation Commermentioning
confidence: 99%
“…Innovation resources have been shown to mediate the relationship between market orientation and organizational performance (e.g., Han, Kim, & Srivastava, 1998). Cravens and Guilding (2000) and Matear, Osborne, Garrett, and Gray (2002) suggested that reputational resources may also mediate this relationship. We propose and test a conceptual model in which the infl uence of market orientation on fi nancial and market performance is mediated through reputational and innovation resources.…”
Section: Cette éTude Examine Les Relations Entre L'orientation Commermentioning
confidence: 99%
“…Higher entrepreneurial orientation that is developed by a company will make the market orientation and company's performance higher. Matear et al,(2002) suggests that market orientation can contribute as a mediating variable in the effect of entrepreneurial orientation towards company's performance. Market orientation can mediate the effect of entrepreneurial orientation towards company's performance.…”
Section: The Effect Of Customer Orientation Andmentioning
confidence: 99%
“…According to Matear, Osborne, Garrett and Gray (2002), the relationship between market orientation and innovation has received continuous attention. Hence, Hult and Ketchen (2001) hypothesized that market orientation, which is an essential marketing capability, enables firms to gain competitiveness and achieve superior performance.…”
Section: Market Orientation and Firm Performancementioning
confidence: 99%
“…Service innovation, market orientation, firm performance, and mediation effect An increasing number of arguments regarding market orientation and service innovation leading to business performances have become critical in business strategy (Avlonitis et al, 2001;Matear et al, 2002;Porter, 2008;Weerawardena, 2003). Consequently, firms must adopt greater innovation, including new operations, services, customers, and markets, to remain competitive (Avolnitis et al, 2001).…”
Section: Hypothesis 2: Market Orientation Positively Relates To Servimentioning
confidence: 99%